Grant Support for the Development of Peasant Farms: The Experience of Sverdlovsk Industrial Region, Problems and Prospects - KRUZHKOVA, Tatiana; KUHAR, Viktor; KOT, Ekaterina; TEREKHOVA, Olga; RUCHKIN, Aleksey; RUSHITSKAYA, Olga (Journal of Environmental Management and Tourism, 2020)
Purpose: the article provides a comprehensive analysis of the use of grants for peasant / farm enterprises by the state authorities of the region (subject of the Russian Federation) in order to create and develop a private agricultural and agro-industrial sector. The system approach is used as the main methodological base, statistical and correlation analysis is applied. Analyzing the current legislation at the level of the Russian Federation and the Sverdlovsk region, using statistical data and reporting documents as evidence, the authors verify the results of their research, as well as the reporting documents of authorities. As the main element of scientific novelty, the main administrative and financial problems that hinder the development of peasant / farm farms in the region are identified, which gives a practical result - the definition of the main directions of state policy reform in the field of agriculture. Also, the atvors, conducting a correlation analysis, determined the degree of availability of grants for beginning farmers and developing private farms, determined the efficiency of distribution and return of budget funds aimed at the development of agriculture through grant support.